Soluble phosphatidylinositol phosphodiesterase in normal and denervated fast and slow muscles of the rat. - Shute, J K (1984)
Phosphatidylinositol phosphodiesterase activity was determined in cytosol prepared from rat slow (soleus) and fast (extensor digitorum longus) muscles. The substrate was prepared by incubation of sarcoplasmic reticulum with myo-[2-3H]inositol. The enzyme hydrolysed both membrane-bound and extracted phosphatidylinositol. The activity determined with the isolated phospholipid exhibited an optimum at pH 5.5. Ca2+ ions stimulated the activity. The enzyme specific activity was higher in cytosol prepared from soleus muscle than in that from extensor digitorum longus muscle. After section of the motor nerve, the activity of the enzyme increased in both muscles up to 36 h and then declined. A function for this enzyme in the control of acetylcholine sensitivity in muscle is discussed.